Benefits of flipped learning approach in improving writing skills - Che Mohd Sabri, Nur Syarafina; Zainal, Syamimi Nursyafikah; Jusoh, Nurul Husna; Abd Rahman, Siti Fatimah (Human Resource Management Academic Research Society, 2023)
The flipped learning approach (FLA) has gained significant popularity since the onset of the COVID-19 pandemic in 2019. Even though flipped learning has become more popular, there is limited research on how well it improves writing skills. This review aims to recognise the benefits of FLA in improving writing skills from learners’ perspectives of different ages and academic levels by reviewing 18 articles and journals from 2019 to 2023. The findings suggest that learners considered FLA as beneficial for enhancing their writing skills, fostering autonomous learning, increasing motivation in writing, and promoting active classroom engagement. This literature review aims to provide a better overview of the benefits of FLA in improving learners' writing skills and recommendations to future researchers to explore more benefits of FLA in improving writing skills from both learners’ and instructors’ perspectives.